Challenges and Opportunities for Developing Islamic Pension Funds in the Global Market - Masruroh; Taufiqur Rahman (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2026)
The development of Islamic finance in Indonesia has increased significantly, but the Islamic pension fund subsector remains slow. This is despite the high growth of the global Islamic economy and Indonesia's large Muslim population, which should present significant opportunities for the development of Sharia-compliant pension instruments. This study aims to identify and analyze the challenges and opportunities for developing Sharia-compliant pension funds in Indonesia using a Systematic Literature Review (SLR) approach, as a basis for strategic policy in building the future of national Islamic finance. The qualitative SLR approach was based on the PRISMA method. Literature from 2015–2025 was collected through Google Scholar, SINTA, and GARUDA. Articles meeting the inclusion criteria were thematically analyzed to identify regulatory, institutional, innovation, and socio-literacy issues. The main challenges are the immature legal framework, low literacy on Sharia pensions, and limited innovative products. Opportunities include support from Muslim demographics, government incentives, and the involvement of Islamic financial institutions.